2001
DOI: 10.1034/j.1398-9995.2001.00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐onset asthma is associated with self‐reported mold or environmental tobacco smoke exposures in the home

Abstract: This population-based case-referent study indicates that self-reported domestic exposures to molds or environmental tobacco smoke can be associated with adult-onset asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
5
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 25 publications
5
83
5
1
Order By: Relevance
“…52 The finding that active tobacco smoking is associated with significantly increased risk of asthma is also consistent with previous research. [53][54][55][56] However, active tobacco smoking is not a major confounder in this study because only a small proportion of women in India smoke tobacco (only 2.3% in the NFHS-2 sample). 4 A positive significant effect of biomass fuel use on asthma is also consistent with previous research linking cooking smoke to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…52 The finding that active tobacco smoking is associated with significantly increased risk of asthma is also consistent with previous research. [53][54][55][56] However, active tobacco smoking is not a major confounder in this study because only a small proportion of women in India smoke tobacco (only 2.3% in the NFHS-2 sample). 4 A positive significant effect of biomass fuel use on asthma is also consistent with previous research linking cooking smoke to asthma.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study of schoolchildren in Japan 24 found a significant association between the prevalence of respiratory symptoms and indoor nitrogen dioxide in girls but not in boys. A Swedish study, 25 however, reported an essentially similar risk of asthma related to visible mold growth among men (OR: 2.7) and women (OR: 2.0). Pershagen et al 26 also suggested that environmental exposure did not differ between boys and girls.…”
Section: E392mentioning
confidence: 99%
“…Anecdotal association of asthma with cooking smoke is common, but few epidemiologic studies seem to have been done (25). Of the limited research that does exist on this issue, some studies have found a positive association between biomass fuel exposure and asthma (10,(54)(55)(56)(57)(58), whereas others found no significant relationship (48,59,(60)(61) or found a protective effect (62,63).…”
Section: Introductionmentioning
confidence: 99%